Investigation of physico-chemical and rheological properties of dairy systems rehydrated using cavitation disintegration - D. A. Salmanova (Современная наука и инновации)
The formation of physicochemical and rheological properties of the rehydrated dairy systems «skimmed milk powder – demineralized whey powder» was studied depending on the parameters and duration of ultrasonic treatment, as well as on the percentage of replacement in solutions of skimmed milk powder with dry demineralized whey. Ternary surfaces are obtained, as well as mathematical models in the form of regression equations describing the formation of the studied properties of the reduced solutions. Optimal treatment modes were determined, as well as the percentage of replacement of skimmed milk powder with dry demineralized whey.